PERAN KNOWLEDGE SHARING DAN LEARNING ORGANIZATION TERHADAP KINERJA PEGAWAI INSPEKTORAT DAERAH KABUPATEN ROKAN HULU - Ananda Sri Rizky Insani (Hirarki : Jurnal Ilmiah Manajemen dan Bisnis, 2024)
This research aims to determine the influence of the role of knowledge sharing andlearning organizations on the performance of Rokan Hulu Regency Regional Inspectorateemployees. Hypothesis testing in this research uses multiple linear regression analysis tools withthe t test, F test and coefficient of determination (R2). The population of this study was all 57employees of the Regional Inspectorate of Rokan Hulu Regency. The sampling technique usessaturated sampling (census). Data collection techniques in this research used documentationmethods, interview methods and questionnaire methods. Based on the results of the research anddiscussion, partial results showed that knowledge sharing had a significant effect on employeeperformance with a value of tcount > ttable 36.103 > 2.00404, learning organization had asignificant effect on employee performance with a value of tcount > ttable (-) 7.432 > 2.00404.Simultaneously, the results obtained are Fcount > Ftable (1859.515 > 3.17), so Ha is accepted andHo is rejected, which means that knowledge sharing and learning organization have a significanteffect on employee performance.